First record of collared peccary (Pecari tajacu) in the southern part of the Mexican Altiplano - Carrasco-Ortiz, Marco A.; Riojas-López, Mónica E.; Mellink, Eric (Therya Notes, 2021)
The collared peccary (Pecari tajacu) is found from northern Argentina to the southern United States. In México it is widely distributed in different habitats, mainly in tropical areas. In the southern portion of the Mexican Altiplano its historic distribution is unclear, and it has been considered extirpated due to the overexploitation of its populations and the development of agriculture. We report the first record of collared peccary for the Llanos de Ojuelos, obtained with a trail camera placed in xeroriparian habitat. This finding confirms the reports of inhabitants about the presence of peccary in the region, approximately 20 km north of the record reported here. There are two recent records of the species in the municipalities of Pinos, Zacatecas and Corral de Palmas, San Luis Potosí, about 60 km from ours, and based on that, the three records and verbal information from peasants appear to refer to different herds. The site of the record reported here is a wash with dense cover by trees and shrubs, surrounded by grassland and xeric scrubland with abundant nopales that provide the peccaries with food and water. The presence of the peccary and other mammals, like puma and deer, in Los Llanos de Ojuelos can be used to implement awareness campaigns among the inhabitants to promote the conservation of the natural resources of the region.